Usability of Mobile Learning Technologies in Open and Distance Learning - Rafifing, Neo; Mosinki, Joyce; Mabina, Alton; Otlhomile, Boitshoko E; Mphole, Ofaletse (Universitas Bina Darma, 2025)
Mobile learning (m-learning) utilizes portable devices like smartphones and tablets for educational purposes and is gaining popularity, particularly in open and distance learning (ODL) contexts. This study explores the usability of mobile learning technologies among undergraduate students in ODL. An online survey questionnaire was administered to undergraduates enrolled in a Business course in Botswana and a usability conceptual model was developed. The findings revealed that predominant opportunities of using mobile learning technologies in ODL include improved student interaction and flexible learning schedules. Likewise, challenges embraced limited battery life, small screens, distractions from phone calls and notifications, and the high cost of internet bundles. To enhance adoption of mobile learning, the study recommends investments in infrastructure and internet connectivity. Furthermore, it suggests reducing internet costs through initiatives like government subsidies or partnerships with Telecom providers. Additionally, the study highlights the importance of training ODL educators and students in effective mobile learning technology utilization.